Stairs Designed for People with Special Needs - Tedi Kurniawan (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this paper is to explain the standard for stairs for people with special needs. This study was based on a literature review from various sources, particularly sources in Indonesia. Detailed examples on how to design stairs were presented. This study is hopefully used as a reference and a guide for architectural and environmental construction, particularly in hospitals, schools, and public facilities for people with special needs (i.e. wheelchairs, crutches, and canes for the blind).